Performance of a small array of Imaging Air Cherenkov Telescopes sited in Australia. (13th September 2022) - Lee, Simon; Einecke, Sabrina; Rowell, Gavin; Balazs, Csaba; Bellido, Jose A.; Dai, Shi; Elsässer, Dominik; Filipović, Miroslav; Harvey, Violet M.; McGee, Padric; Rhode, Wolfgang; Tingay, Steven; et al.
Abstract: As TeV gamma-ray astronomy progresses into the era of the Cherenkov Telescope Array (CTA), there is a desire for the capacity to instantaneously follow up on transient phenomena and continuously monitor gamma-ray flux at energies above $10^{12}\, eV$ . To this end, a worldwide network of Imaging Air Cherenkov Telescopes (IACTs) is required to provide triggers for CTA observations and complementary continuous monitoring. An IACT array sited in Australia would contribute significant coverage of the Southern Hemisphere sky. Here, we investigate the suitability of a small IACT array and how different design factors influence its performance. Monte Carlo simulations were produced based on the Small-Sized Telescope (SST) and Medium-Sized Telescope (MST) designs from CTA. Angular resolution improved with larger baseline distances up to 277 m between telescopes, and energy thresholds were lower at 1 000 m altitude than at 0 m. The ${\sim} 300\, GeV$ energy threshold of MSTs proved more suitable for observing transients than the ${\sim}1.2\, TeV$ threshold of SSTs. An array of four MSTs at 1 000 m was estimated to give a 5.7 $σ$ detection of an RS Ophiuchi-like nova eruption from a 4-h observation. We conclude that an array of four MST-class IACTs at an Australian site would ideally complement the capabilities of CTA.